Hedonic Test Of Lado Mudo Chili Sauce By Addition Of Various Concentrations Of Citric Acid - Dea Tio Mareta; Hesti Ayuningtyas Pangastuti; Lasuardi Permana; Vita Fitriani; Amalia Wahyuningtyas (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2021)
The chili sauce product is very popular because it is practical and easy to carry anywhere, and has a longer shelf life compared to fresh chili sauce. This study aimed to determine the level of consumer acceptance by the preference test (hedonic) of some of the sensory attributes of lado mudo chili sauce (color, aroma, texture, and taste) with variations in the addition of citric acid concentration (0% w/w), 0.1%. (w/w), 0.3% (w/w), and 0.5% (w/w)). The hedonic test of lado mudo chilli sauce involved 30 untrained panelists, using a rating scale in the form of numbers from 1 (Dislike Extremely) to 9 (Like Extremely). The results showed that the panelists' preference for the sensory attributes of color, texture, aroma, texture and taste led to the descriptions of " Like Slightly", "Neither Like nor Dislike", " Neither Like nor Dislike ", and " Neither Like nor Dislike", while variations in the addition of citric acid were not affect the level of preference for all sensory attributes of the panelists